The function of labour market mobility to regional economic growth generally and by new service economy and labour force nationality especially - Lasse Sigbjørn Stambøl (European Regional Science Association (ERSA), 2005)
Efficient matching of local demand and supply of labour at different qualification levels is considered to be an important prerequisite for economic growth in every region. The expectation is that higher mobility of the labour force should increase the general level of employment, e.g. due to a relatively high gross demand of labour and the problems of matching-time to fill in the vacancies. Moreover, increased total labour mobility is thus seen as one tool for reaching the goals of the labour market policy, employing as large as possible part of the labour force into ordinary employment. Use of annual gross-flow labour market statistics may be very relevant in such analyses, allowing multidimensional analysis of labour market mobility, i.e. in geographical terms as well as between sectors and according to the qualifications of the labour force. Among the sectors, knowledge intensive business services (KIBS) are often seen as an important characteristic of the new, more knowledge based economy. Efficient sharing and transferring of knowledge is central, and KIBS play an important role in the learning and transaction processes. It is thus of importance to analyse KIBS' role as a regional competitive base, e.g. by studying the competitiveness of cities and regions in terms of growth of employment, and particularly focus on the mobility of the individuals that enter and leave the KIBS sectors. Labour mobility in this growing sector may also act as a prerequisite for what may be expected to form the future labour mobility structures of the society, and is thus of particular importance for both the labour market and regional policy perspectives. Increased international migration as a result of increased internationalisation gives rise to a more internationally mixed labour force within countries. On the other hand, national labour market policy attempt to use actively immigration as a tool for solving parts of the domestic labour market problems, e.g. shortage of supply of certain kinds of labour in more remote regions. It is thus of particular importance to analyse the function of both initial and succeeding labour mobility among different immigrant groups and how their labour mobility function in relation to the mobility of the employed national majority. The main purpose of this paper is to present some analyses of the regional labour mobility in terms of growth of employment focusing on the number and quality of the persons that enter and leave the local labour markets. Besides some descriptive analyses, we test the hypothesis if the regional growth of employment is positively or negatively correlated to the level of different segments of gross mobility to and from jobs generally, and more particularly for employment in knowledge intensive service industries and for the employment broken down by different groups of nationality.
Keywords: 330